The Dependence of Boron Concentration in Diamond Electrode for Ciprofloxacin Electrochemical Sensor Application - Ilmi Nur Indriani Savitri; Prastika Krisma Jiwanti; Ilmanda Zalzabhila Danistya Putri; Irkham Irkham; Yasuaki Einaga; Ganden Supriyanto; Yew Hoong Wong; Sachin Kumar Srivastava; Che Azurahanim Che Abdullah (Indonesian Journal of Chemistry, 2023)
This study investigates the effects of boron concentration on boron-doped diamond (BDD) electrodes for electrochemical sensors of ciprofloxacin. The effects of boron concentration, scan rate, and pH of BDD electrodes with boron concentrations of 0.1, 0.5, and 1% were examined to determine the optimal conditions. Furthermore, square wave voltammetry (SWV) in phosphate buffer pH 7 was used to analyze the electrochemical behavior of ciprofloxacin. The results revealed a linear calibration curve in the concentration range of 30–100 μM with a recovery of 85–110%. Meanwhile, BDD electrode with the highest boron concentration in this experiment (1%) showed a very low limit of detection of 0.17 μM, meaning that 1% BDD gave a highly sensitive and significant measurement result for the electrochemical sensor of ciprofloxacin. With the results given, this study provides new insights for controlling boron concentrations in diamond electrodes for the electrochemical sensors of quinolone antibiotics.